A study on the influence-of personality towards employee's performance in Pejabat Pendidikan Daerah Pekan / Nurul Farhanah Mohamad Lokeman - Mohamad Lokeman, Nurul Farhanah (Faculty of Business and Management, 2018)
This research was conducted to employees at Pejabat Pendidikan Daerah (PPD) Pekan to study the influence of personality towards employee's performance. The objective of this research are to identify the most personality traits that contribute towards employee's performance and to investigate the relationships between personality and employee's performance. Hence, this research focuses on the big five personality behaviour which are conscientiousness, agreeableness, neuroticism, openness to experience and extroversion. Furthermore, the researcher was used the descriptive statistic method to key in the data from questionnaire to get the result of data analysis using the Statistical Package in the Social Science Software (SPSS) version 21. The researcher was distributing the questionnaire to 56 respondents in this government sector that has been chosen for this study. Based on the findings, the researcher was found the relationships between dependent variable and independent variable for this study. Besides, the researcher was made several recommendations in order to improve the employee's performance at this government sector. Other than that, the researcher also made some recommendation for future research to improve the research in the future.